Hidden Curriculum dalam Pendidikan Pesantren: Membentuk Keterampilan Seni Santri melalui Program Kaligrafi di Pondok Pesantren Darussalam Bermi - Sofiyan Baehaki; Akhmad Syahri; Mustain (Mataram University, 2026)
This study examines the concept, role, and implementation of the hidden curriculum at the Darussalam Bermi Islamic Boarding School in West Lombok, and attempts to establish continuity between formal and non-formal education. Using a qualitative approach with field research, data were collected through observation, in-depth interviews, and documentation. The results indicate that the hidden curriculum in Islamic boarding schools is a set of unwritten values, norms, and customs learned by students through interaction, role models, and habituation. Its role is crucial in developing students' artistic skills, independence, creativity, discipline, and responsibility. Its implementation is manifested through a calligraphy art program (limited class hours and a weekly program), independent student practice in their free time, and support from the Islamic boarding school in the form of space, facilities, and appreciation for students' work. Integrated continuity between formal and non-formal education can be achieved by consciously and deliberately managing the hidden curriculum, making character a part of students' daily lives.